Conditions of carved furniture entrepreneurs in Telukawur Village, Jepara: between expectations and reality - Thohir, Mudjahirin (Proceedings International Conference of Culture and Sustainable Development; Vol 1 (2023): PROCEEDINGS ICOCAS, 2023)
The people of Teluk Awur Jepara actually benefit from some of their potential. Among other things, the location of this village has the campus of Diponegoro University, sea tourism, and the people are known as furniture (carving) craftsmen. However, these various potentials have not shown maximum utilization, especially in carving, so that there are still many furniture entrepreneurs who have gone out of business and changed other businesses. Such conditions, invite curiosity to be explored, what causes it? For this reason, this study is focused on gathering data through personal interviews and focus group discussions with carver craftsmen, to find problems and solutions that they have been pursuing, as well as what empowerment model is considered appropriate.